Dehydration and other strategies of rapid weight loss in young powerlifters - Kruszewski, M.; Pagowski, L.; Kruszewski, A.; Tabecki, R.; Merchelski, M. (Journal of Kinesiology and Exercise Sciences, 2022)
Background: Prevalence of dehydration as a method of rapid weight loss (RWL) and related risks point to the necessity of knowledge assessment in young powerlifters in this regard. The aim of this study was to assess practices and knowledge about RWL methods and their potential detrimental effects on health in young powerlifters. Materials and methods: A diagnostic poll was carried out among the participants (n=98) of sub-junior Polish championships (14 - 18 years), in two subgroups: G1 - weight classes up to 75 kg (n=50) and G2 - weight classes above 75 kg (n=48). Results: Dehydration was most frequently indicated by young powerlifters as a method of body weight reduction in young powerlifters whereas diuretics, potentially hazardous to health, were the most popular supplement. Conclusions: Despite popular belief that extreme RWL methods are most prevalent in lighter weight classes, athletes of higher weight classes more frequently indicated the methods with high risk of dehydration. Among young powerlifters, knowledge of the consequences of RWL is inadequate.